ACCUMULATIVE SAFETY PERIOD OF PREMISES IN THE CASE OF THEIR POLLUTION WITH TOXIC MERCURY VAPORS - Dmitrucha, Tatyana (Proceedings of National Aviation University (archive), 2014)
An ecological indicator is determined - accumulative period of safety in premises which means duration of the relative safety of the premises after occurrence of their pollution with mercury vapor or other toxic substances.